Cost utility analysis of co-prescribed heroin compared with methadone maintenance treatment in heroin addicts in two randomised trials - Dijkgraaf, Marcel G W (BMJ Publishing Group Ltd., 2005)
Objective To determine the cost utility of medical co-prescription of heroin compared with methadone maintenance treatment for chronic, treatment resistant heroin addicts. Design Cost utility analysis of two pooled open label randomised controlled trials. Setting Methadone maintenance programmes in six cities in the Netherlands. Participants 430 heroin addicts. Interventions Inhalable or injectable heroin prescribed over 12 months. Methadone (maximum 150 mg a day) plus heroin (maximum 1000 mg a day) compared with methadone alone (maximum 150 mg a day). Psychosocial treatment was offered throughout. Main outcome measures One year costs estimated from a societal perspective. Quality adjusted life years (QALYs) based on responses to the EuroQol EQ-5D at baseline and during the treatment period. Results Co-prescription of heroin was associated with 0.058 more QALYs per patient per year (95% confidence interval 0.016 to 0.099) and a mean saving of €12 793 (£8793, $16 122) (€1083 to €25 229) per patient per year. The higher programme costs (€16 222; lower 95% confidence limit €15 084) were compensated for by lower costs of law enforcement (- €4129; upper 95% confidence limit - €486) and damage to victims of crime (- €25 374; upper 95% confidence limit - €16 625). The results were robust for the use of national EQ-5D tariffs and for the exclusion of the initial implementation costs of heroin treatment. Completion of treatment is essential; having participated in any abstinence treatment in the past is not. Conclusions Co-prescription of heroin is cost effective compared with treatment with methadone alone for chronic, treatment resistant heroin addicts.